Preferensi Petani dalam Memilih Usahatani Komoditas Cabe Rawit dan Cabe Merah Besar di Kota Tasikmalaya - Pujianti Dini Lestari; Reny Hidayati; Ristina Siti Sundari (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2023)
Cayenne pepper and large red chili are complementary food commodities that are always needed, and their prices fluctuate. This research was conducted to determine farmers' preferences in choosing large red chilies and cayenne peppers. The method used in this study was conjoint analysis which was used to analyze the preferences of 36 farmers in selecting large red chilies and cayenne pepper. Commodity levels of importance no. 1 and no. 2 are the same regarding resistance to pests and diseases and market prospects. For the following order, it is a difference between sizeable red chili and cayenne pepper commodities. In terms of the combination of attribute levels, the utility estimate value between the two commodities has different values, so a correlation test is produced where the significant value of Pearson and Kendall's bird's eye chili is smaller than 0.05 compared to large red chili. High pests, long plant life, high input prices, ease of obtaining seeds compared to large red chilies, and high prices in the market.